Two new cadmium(II) coordination polymers based on imidazole‐containing ligands: synthesis, structural characterization and fluorescence properties. Issue 4 (6th March 2020) - Li, Bing-Feng; Xu, Xi-Ting; Dong, Tong-Min; Zhou, Wan-Ying; Gu, Yang; Gong, Lei; Zhong, Kai-Long
Abstract : Two Cd II coordination polymers have been synthesized from 1, 4‐bis[(1 H ‐imidazol‐1‐yl)methyl]benzene and 1, 3, 5‐tris[(1 H ‐imidazol‐1‐yl)methyl]benzene ligands, forming a distorted seven‐coordinated pentagonal bipyramidal geometry and a one‐dimensional ladder chain with the former ligand, and a six‐coordinated octahedral structure with layers connected by hexafluorosilicate anions with the latter. Abstract : The judicious selection of suitable ligands is vitally important in the construction of novel metal–organic frameworks (MOFs) with fascinating structures and interesting properties. Recently, imidazole‐containing multidentate ligands have received much attention. Two new Cd II coordination frameworks, namely, poly[trisμ‐1, 4‐bis[(1 H ‐imidazol‐1‐yl)methyl]benzene‐κ 2 N 3 : N 3′ tetrakis(nitrato‐κ 2 O, O ′)dicadmium], [Cd2 (NO3 )4 (C14 H14 N4 )3 ] n, (I), and poly[[bisμ3 ‐1, 3, 5‐tris[(1 H ‐imidazol‐1‐yl)methyl]benzene‐κ 3 N 3 : N 3′ : N 3′′ cadmium] hexafluorosilicate], [Cd(C18 H18 N6 )2 ](SiF6 ) n, (II), have been synthesized and characterized by elemental analysis, IR spectroscopy and single‐crystal X‐ray diffraction. In polymer (I), the 1, 4‐bis[(1 H ‐imidazol‐1‐yl)methyl]benzene ligand bridges Cd 2+ ions with a distorted seven‐coordinated pentagonal bipyramidal geometry, forming a one‐dimensional ladder chain, and the nitrate anions coordinate to the Cd 2+ ions in a terminal bidentate fashion. In the crystal, adjacent chains are further connected by C—H…O hydrogen bonds to generate a two‐dimensional (2D) supramolecular structure. Polymer (II) exhibits a 2D layered structure in which 1, 3, 5‐tris[(1 H ‐imidazol‐1‐yl)methyl] benzene ligands join Cd 2+ centres having a six‐coordinated octahedral structure. The layers are connected by hexafluorosilicate anions via C—H…F hydrogen‐bond interactions, giving rise to a three‐dimensional supramolecular network structure in the solid state. In addition, powder X‐ray diffraction (PXRD) patterns were recorded, thermogravimetric analyses (TGA) carried out and fluorescence properties investigated.